Sunrise to eternity : a study in Jacob Boehme's life and thought - Stoudt, John Joseph, 1911- (University of Pennsylvania Press, 1957)
"An extensive, scholarly, and readable book on Jacob Boehme in English has been long overdue. It has now been provided by John Stoudt in Sunrise to Eternity. For many years his interest was centered around the life and the work of the mystical and philosophical shoemaker and shoetrader of Gorlitz in eastern Germany. As a result of the author's work, we have a concrete and vivid picture, not only of the personal affairs of his hero, but also of the spiritual and cultural situation of Protestant Germany int he early sixteenth century." -- Paul Tillich (Preface, p.7).